A global sensitivity analysis approach applied to a multiscale model of microvascular flow. Issue 15 (17th November 2020) - Possenti, L.; Di Gregorio, S.; Casagrande, G.; Costantino, M. L.; Rancati, T.; Zunino, P.
Abstract: A global sensitivity analysis of a multiscale computational model of microvascular flow is presented. A total of 140 simulations have been completed and analyzed varying 6 input parameters and considering their effects on 7 output variables. Interestingly, the vascular network topology has been found as a determinant factor for both vasculature-related and interstitium-related quantities. Regarding the firsts, the vascular network topology has obtained a score of 5.5/6 and 6/6 for average and spatial distribution respectively (where 6 is the maximum and 1 is the minimum). On the other hand, considering interstitium-related quantities, the score is 4/6 and 5/6 for average and spatial distribution respectively. These results suggest that the network topology has a significant influence on the outcome of the computational analysis.